Sāmaẏikapatre Rabīndraprasaṅga : Śāntiniketana, Baiśākha 1326-Kārtika 1333 - Mitra, Supti (Ṭegora Risārca Inashṭiṭiuṭa, 1980)
On the Indian poet Rabindranath Tagore, 1861-1941, and Santiniketan, seat of learning founded by Tagore; collection of excerpts from the institution's journal Śāntiniketana, 1919-1926.